Bioattenuation of phenol and cyanide involving immobilised spent tea activated carbon with Alcaligenes faecalis JF339228: Critical assessment of the degraded intermediates. Issue 1 (21st December 2018) - Pathak, Uttarini; Roy, Ananya; Mandal, Dalia Dasgupta; Das, Papita; Kumar, Tarkeshwar; Mandal, Tamal
Abstract: The current study is designed for the eradication of phenol and cyanide from a simulated binary mixture involving acetic acid modified spent tea activated carbon (STAC‐C), isolated bacterial strain Alcaligenes faecalis JF339228, and immobilized A. faecalis JF339228 onto spent tea biochar by an amalgamated approach of sorption coupled with biodegradation. Characterisation of the biosorbent was ascertained by field emission scanning electron microscopy, thermogravimetric analysis, and Fourier transform infrared spectroscopy. The viability for eco‐benign expulsion of the pernicious pollutants, and the resultant compounds after treatment was examined by fluorescence and UV‐visible spectrophotometry with comprehensive elucidation of the interactions with DNA. Gas chromatography–mass spectrometry (GC‐MS) anatomization was conducted for the evaluation of degraded derivatives post‐treatment. The chemical and structural analysis of the degraded compounds and its impact upon disposal on the basis of degree of toxicity and reactivity were evaluated using TOXTREE software. Batch studies were implemented for the evaluation of process parameters like pH, reaction time, biosorbent or inoculum dosage, initial concentration, and temperature. Mono and binary component isotherm modelling was executed. Immobilised cells and free cells could accomplish better removal efficacy of 94.71% and 92.25% for cyanide, respectively, whereas adsorption using STAC‐C was responsible for maximum removal of phenol up to 86.29%.